Celebratory consumerism on China's Singles' Day: From grass-roots holiday to commercial festival. (August 2019) - Sun, Weimei; Creech, Brian
Singles' Day, or 11 November, was initially conceived as a way to celebrate singlehood among Chinese youth. Since 2009, the e-commerce giant Alibaba has transformed Singles' Day into the world's largest online shopping day, using its discursive power to define the day as overtly commercial. To analyse emerging consumerist discourses around Singles' Day, we considered news coverage alongside posts on Sina Weibo. Although the Singles' Day bent towards consumerism occurred over time, in concert with demographic and political changes within China, our research shows that consumerist understandings of Singles' Day emerged from a nascent cultural logic that celebrated togetherness through consumption.